2005
DOI: 10.1124/jpet.105.090621
|View full text |Cite
|
Sign up to set email alerts
|

General Anesthetic-Induced Channel Gating Enhancement of 5-Hydroxytryptamine Type 3 Receptors Depends on Receptor Subunit Composition

Abstract: 5-Hydroxytryptamine (serotonin) (5-HT) type 3 (5-HT 3 ) receptors are members of an anesthetic-sensitive superfamily of Cys-loop ligand-gated ion channels that can be formed as homomeric 5-HT 3A or heteromeric 5-HT 3AB receptors. When the efficacious agonist 5-HT is used, the inhaled anesthetics halothane and chloroform (at clinically relevant concentrations) significantly reduce the agonist EC 50 for 5-HT 3A receptors but not for 5-HT 3AB receptors. In the present study, we used dopamine (DA), a highly ineffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 24 publications
2
32
0
Order By: Relevance
“…In addition, the peak amplitudes of currents evoked by high concentrations of DA were only 15.7 Ϯ 0.4% of those evoked by high concentrations of 5-HT. This is consistent with previous studies using 5-HT 3A receptors expressed in Xenopus oocytes, indicating that DA is a partial agonist of 5-HT 3A receptors (Lovinger et al, 2000;Solt et al, 2005).…”
Section: Activation Of Human 5-ht 3a Receptorssupporting
confidence: 82%
See 1 more Smart Citation
“…In addition, the peak amplitudes of currents evoked by high concentrations of DA were only 15.7 Ϯ 0.4% of those evoked by high concentrations of 5-HT. This is consistent with previous studies using 5-HT 3A receptors expressed in Xenopus oocytes, indicating that DA is a partial agonist of 5-HT 3A receptors (Lovinger et al, 2000;Solt et al, 2005).…”
Section: Activation Of Human 5-ht 3a Receptorssupporting
confidence: 82%
“…In addition to 5-HT, the neurotransmitter dopamine (DA) can activate 5-HT 3 receptors. Studies using oocyte electrophysiological techniques indicate that, in contrast to 5-HT, DA gates 5-HT 3 receptors with low efficacy because peak currents evoked by receptor-saturating concentrations of DA are significantly smaller than those evoked by 5-HT (Lovinger et al, 2000;Solt et al, 2005). These studies also show that the potency of DA is one to two orders of magnitude lower than that of 5-HT.…”
Section: Introductionmentioning
confidence: 59%
“…These studies found that both anesthetics exert at least some of their modulating effects on GABA A receptors by enhancing channel gating. More recently, the potentiating effects of small volatile anesthetics on 5-HT 3A and 5-HT 3AB were studied electrophysiologically using DA (Solt et al, 2005). The results of that study parallel our findings with alcohols in the present study: 1) volatile anesthetics potentiate receptor function by enhancing gating efficacy, and 2) gating enhancement is dependent on receptor subunit composition with the magnitude of gating enhancement being greater in 5-HT 3A relative to 5-HT 3AB receptors.…”
supporting
confidence: 79%
“…The 5-HT and DA concentration ranges were chosen based on previous studies (Solt et al, 2005;Stevens et al, 2005a,b). The duration of 5-HT and DA application was varied from 15 to 60 s, depending upon the concentration of agonist studied, to achieve a peak current response.…”
Section: Experimental Protocolsmentioning
confidence: 99%
“…It has been proposed that these compounds stabilize the open state of 5-HT 3A channels (Zhou and Lovinger, 1996;Zhou et al, 1998;Lovinger et al, 2000;Solt et al, 2005). However, this hypothesis could never be directly measured due to the small single-channel conductance of the 5-HT 3A receptor.…”
mentioning
confidence: 99%